If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90(x + 24) + 90(x) = 4x(x + 4) Reorder the terms: 90(24 + x) + 90(x) = 4x(x + 4) (24 * 90 + x * 90) + 90(x) = 4x(x + 4) (2160 + 90x) + 90(x) = 4x(x + 4) Combine like terms: 90x + 90x = 180x 2160 + 180x = 4x(x + 4) Reorder the terms: 2160 + 180x = 4x(4 + x) 2160 + 180x = (4 * 4x + x * 4x) 2160 + 180x = (16x + 4x2) Solving 2160 + 180x = 16x + 4x2 Solving for variable 'x'. Combine like terms: 180x + -16x = 164x 2160 + 164x + -4x2 = 16x + 4x2 + -16x + -4x2 Reorder the terms: 2160 + 164x + -4x2 = 16x + -16x + 4x2 + -4x2 Combine like terms: 16x + -16x = 0 2160 + 164x + -4x2 = 0 + 4x2 + -4x2 2160 + 164x + -4x2 = 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 2160 + 164x + -4x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(540 + 41x + -1x2) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(540 + 41x + -1x2)' equal to zero and attempt to solve: Simplifying 540 + 41x + -1x2 = 0 Solving 540 + 41x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -540 + -41x + x2 = 0 Move the constant term to the right: Add '540' to each side of the equation. -540 + -41x + 540 + x2 = 0 + 540 Reorder the terms: -540 + 540 + -41x + x2 = 0 + 540 Combine like terms: -540 + 540 = 0 0 + -41x + x2 = 0 + 540 -41x + x2 = 0 + 540 Combine like terms: 0 + 540 = 540 -41x + x2 = 540 The x term is -41x. Take half its coefficient (-20.5). Square it (420.25) and add it to both sides. Add '420.25' to each side of the equation. -41x + 420.25 + x2 = 540 + 420.25 Reorder the terms: 420.25 + -41x + x2 = 540 + 420.25 Combine like terms: 540 + 420.25 = 960.25 420.25 + -41x + x2 = 960.25 Factor a perfect square on the left side: (x + -20.5)(x + -20.5) = 960.25 Calculate the square root of the right side: 30.987900865 Break this problem into two subproblems by setting (x + -20.5) equal to 30.987900865 and -30.987900865.Subproblem 1
x + -20.5 = 30.987900865 Simplifying x + -20.5 = 30.987900865 Reorder the terms: -20.5 + x = 30.987900865 Solving -20.5 + x = 30.987900865 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20.5' to each side of the equation. -20.5 + 20.5 + x = 30.987900865 + 20.5 Combine like terms: -20.5 + 20.5 = 0.0 0.0 + x = 30.987900865 + 20.5 x = 30.987900865 + 20.5 Combine like terms: 30.987900865 + 20.5 = 51.487900865 x = 51.487900865 Simplifying x = 51.487900865Subproblem 2
x + -20.5 = -30.987900865 Simplifying x + -20.5 = -30.987900865 Reorder the terms: -20.5 + x = -30.987900865 Solving -20.5 + x = -30.987900865 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20.5' to each side of the equation. -20.5 + 20.5 + x = -30.987900865 + 20.5 Combine like terms: -20.5 + 20.5 = 0.0 0.0 + x = -30.987900865 + 20.5 x = -30.987900865 + 20.5 Combine like terms: -30.987900865 + 20.5 = -10.487900865 x = -10.487900865 Simplifying x = -10.487900865Solution
The solution to the problem is based on the solutions from the subproblems. x = {51.487900865, -10.487900865}Solution
x = {51.487900865, -10.487900865}
| 14.5y=6 | | 21nx-3=0 | | 7a+2=5a+3 | | 7x-10=3(x-2)+5(x-1) | | 95=-47-4(t+6) | | -2x+9y=-6 | | 10-6x-9x+3= | | 8(2c+2)= | | 27(x-1)=3(2x) | | 8y+56=15y | | 20-2v=3v | | 90(x+4)+15(x)=4x(x+4) | | 30+x=7x | | 3y=-15x+270 | | -38+8x=2(8x+1)+8 | | t=0.25(i-32720)+4867.5 | | 4x^2-89x-360=0 | | 6v-5v=3v+8 | | V^2-121=0 | | x+1+x+9=50 | | 36+7v=13v | | 10x-5y+6=6 | | 3(1+6m)=-16-m | | 0.03-0.4x=1.85 | | 7-3(9-x)=16 | | 2(a+6)=5+9 | | 3n^3+10n+16=8 | | 2z^2+5z+3= | | 2b+8(2b-3)=-3(-5b-6) | | -n-21=3(6n-7) | | -2x+19+5x-11=x | | 16+7yi=-8x+i |